A Sandwich Complex of Bismuth Cation and Mono‐Lacunary α‐Keggin‐Type Phosphotungstate: Preparation and Structural Characterisation. Issue 3 (11th October 2018) - Wihadi, Muh Nur Khoiru; Hayashi, Akio; Ichihashi, Katsuya; Ota, Hiromi; Nishihara, Sadafumi; Inoue, Katsuya; Tsunoji, Nao; Sano, Tsuneji; Sadakane, Masahiro
Abstract : We report the first Peacock–Weakley type complexes composed of mono‐lacunary Keggin‐type phosphotungstate, [α‐PW11 O39 ] 7–, and Bi 3+ . The self‐assembly reaction between the Keggin‐type phosphotungstate and Bi 3+ in aqueous solution produced Peacock–Weakley type 2:1 ([(PW11 O39 )2 Bi] 11–, 1 ) and 1:1 ([PW11 O39 Bi] 4–, 2 ) complexes depending on the mixing ratio of [α‐PW11 O39 ] 7– and Bi 3+ . Studies of both complexes in solution were conducted by different NMR techniques including 31 P and 183 W analyses. Complex1 was successfully isolated as both tetramethyl ammonium (1a ) and potassium (1b ) salt, and characterized by single‐crystal X‐ray diffraction, IR spectroscopy and elemental analysis. The sandwich structure of1a and1b was determined to be constructed by eight Bi–O bonds with two [α‐PW11 O39 ] 7– units. Abstract : Bismuth (Bi 3+ ) can form Peacock and Weakley‐type 1:2 and 1:1 complexes with mono‐lacunary Keggin‐type phosphotungstates, which is confirmed by 31 P NMR, 183 W NMR, single crystal structure analysis, IR and elemental analysis.